Moderate Septoria apocyni infection enhances flavonoid and mineral elements accumulation in Apocynum venetum leaves - Panpan Shang; Yanglu Ran; Xinchun Ge; Li Wang; Meiting Bai; Jiming Yang; Yonghe Cai; Tingyu Duan (Plant Stress)
Apocynum venetum, a perennial herbaceous plant widely utilized in traditional Chinese medicine and tea production, encounters significant growth constraints due to spot blight caused by Septoria apocyni. While the impact of this fungal infection on the plant's growth is evident, its effect on the chemical and nutrient composition of the leaves remains poorly explored. This study employed transcriptomics technology to elucidate the molecular mechanisms underlying the response of A. venetum to spot blight, while simultaneously investigating flavonoid and mineral elements content of the leaves. Our findings show that the contents of total flavonoids, hyperoside, and rutoside significantly increased by 9.7%, 17.7%, and 5.1%, respectively, at disease severity scale 3 compared to healthy leaves (severity scale 0). Similarly, the concentrations of calcium (Ca), copper (Cu), and iron (Fe) exhibited substantial increases of 21.50%, 54.83%, and 40.17% at disease severity scale 3. Notably, we observed a progressive decrease in amino acid content corresponding with increasing disease severity. Additionally, gene expression patterns in flavonoid biosynthesis and amino acid biosynthesis are altered. Research indicates that mild spot blight stress may potentially enhance plant quality through increased flavonoid and mineral elements concentrations. This study reveals the positive effects of spot blight on leaf quality in medicinal and tea application, demonstrating that moderate fungal infection can enhance beneficial compounds. Our findings provide new insights into plant responses to stress and contribute to the better utilization of medicinal resources.